Theoretical Studies of Sum Optical Properties for InAs (001) by Surface Differential Reflectivity (Baghdad Science Journal, 2007)
The real and imaginary part of complex dielectric constant for InAs(001) by adsorption of oxsagen atoms has been calculated, using numerical analysis method (non-linear least square fitting). As a result a mathematical model built-up and the final result show a fairly good agreement with other genuine published works.